2015
DOI: 10.11131/2015/101121
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructions of Traumatic Lacrimal Canalicular Lacerations: A 5 Years Experience

Abstract: Abstract. Background:The aim of this study is to evaluate the demographic and epidemiological data, clinical features and surgical outcomes of lacrimal canalicular lacerations. Methods: The charts of all patients who applied to our emergency department with eyelid laceration from 2008 to 2013 were reviewed retrospectively. Demographic and epidemiological data, clinical characteristics, treatment outcomes, simultaneous injuries and complications of patients who underwent canalicular laceration repair surgery we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 16 publications
0
19
1
3
Order By: Relevance
“…There is a considerable debate on how long should the lacerated canaliculus be stented but in general the duration of stenting ranged from 3 months to 1 year in most of the studies. (8,16,20,21) In this report stents were left for one year, only removed earlier if complicated. The majority of stents (81.8%) were removed between 3 and 6 months.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is a considerable debate on how long should the lacerated canaliculus be stented but in general the duration of stenting ranged from 3 months to 1 year in most of the studies. (8,16,20,21) In this report stents were left for one year, only removed earlier if complicated. The majority of stents (81.8%) were removed between 3 and 6 months.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies found anatomical canalicular patency with no epiphora when mono-canalicular stents were used for bicanalicular laceration. (8,(16)(17)(18) In this study, 2 patients had bi-canalicular mono-canalicular stents, one in each canaliculus, both had anatomical patency with insignificant epiphora that does not interfere with daily activities or visual acuity.…”
Section: Discussionmentioning
confidence: 90%
“…[15] Success rate of monocanalicular intubation method has been reported in the range of 60% to 100%. [21][22][23]30,32,33] High rate of success has also been described in some studies conducted in our country. Argın et al, [12] Yaman et al, [29] and Oltulu et al reported success rate of 100%.…”
Section: Discussionmentioning
confidence: 94%
“…[13] Şendul et al reported 97% anatomical success and 93% functional success in 44-case series. [33] (Table 3) In present study, anatomical and functional success rate was determined to be 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation